2022
DOI: 10.2106/jbjs.oa.21.00159
|View full text |Cite
|
Sign up to set email alerts
|

The Characterization of Social Media in Orthopaedic Surgery

Abstract: Background: There is a paucity of information regarding the use of social media by both orthopaedic residents and applicants. Therefore, this investigation aimed to (1) characterize the use of social media by current orthopaedic surgery residents and applicants to an orthopaedic surgery residency and (2) evaluate the influence of social media on applicants to an orthopaedic surgery residency. Methods: An anonymous, nationwide survey was conducted among current orthopaedic surgery residents and fourthyear medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In this study, employment-oriented SM, YouTube, and messenger apps, which were the SM platforms used the most for educational purposes, were each used by less than 25% of the participants. In contrast, a study by Schneider et al [31] found among a group of 312 orthopedic residents and medical students that the majority showed a high interest in accessing educational information via SM [31]. This difference may be explained by the fact that the presented study included participants from all age groups and experience levels, and not only residents or medical students who might show a higher affinity to SM due to their younger age.…”
Section: Principal Findingsmentioning
confidence: 60%
See 1 more Smart Citation
“…In this study, employment-oriented SM, YouTube, and messenger apps, which were the SM platforms used the most for educational purposes, were each used by less than 25% of the participants. In contrast, a study by Schneider et al [31] found among a group of 312 orthopedic residents and medical students that the majority showed a high interest in accessing educational information via SM [31]. This difference may be explained by the fact that the presented study included participants from all age groups and experience levels, and not only residents or medical students who might show a higher affinity to SM due to their younger age.…”
Section: Principal Findingsmentioning
confidence: 60%
“…In the health care system, SM is shaping the ways and dimensions of communication and the dissemination and consumption of (health) information [7,30]. The active use and popularity of SM in the professional context was particularly accelerated by the COVID-19 pandemic [31,32]. Several benefits of professional SM use have been previously identified.…”
Section: Principal Findingsmentioning
confidence: 99%
“…In recent published surveys [9][10][11][12][13], the orthopaedic surgery residents and applicants confirmed the wide use of social media in information and learning. The main use was for making choices in residency program and was performed mainly by listening to podcasts.…”
Section: The Social Media Influence and Influencers In Medicinementioning
confidence: 83%
“…There are many studies in the current literature on whether social media is informative and useful in the field of orthopaedics [3,[21][22][23]25]. Many orthopaedic surgeons and journals have at least one social media account, including Instagram, with shoulder and knee surgeons being the most active user groups [5,6,14,20,24,25].…”
Section: Introductionmentioning
confidence: 99%